Variation of metallothionein and metal concentrations in the digestive gland of the clamRuditapes decussatus: sex and seasonal effects - Serafim, Angela (2020)
Metallothionein (MT) and metal (Cd, Cu, and Zn) concentrations were determined in the digestive gland of male and female Ruditapes decussates. Clams were collected monthly during the period of sexual development, from June to September, at two different sites of a coastal lagoon, the Ria Formosa Lagoon, on the south coast of Portugal. The MT concentrations were determined in the heat-treated cytosolic fraction of the digestive gland of both male and female clams. Total metal (Cd, Cu, and Zn) concentrations in the heat-treated cytosol of the digestive gland were also determined in both sexes. The MT and metal concentrations in the digestive gland were not sex dependent in this species. Therefore, these results suggest that random samples can be used to determine MT and metal concentrations in the digestive gland of R. decussatus. Seasonal and site-specific dependency, however, were detected for MT, Cd, and Cu concentrations. The maximum concentration levels of MT, Cd, and Cu were detected in July and August for both sexes in the same area. Zinc concentrations, however, did not show marked seasonal variations, indicating that this species is able to regulate zinc concentrations. The highest MT concentrations were significantly related to the highest metal concentrations.